Numerical analysis of ground improvement using column-like elements - Al-Ani, Wisam (2020)
The issue of constructing foundations and embankments over highly compressible soft soils is of great importance for geotechnical engineers due to their undesirable characteristics such as excessive settlement and low bearing capacity. A number of techniques including column-like elements, such as settlement-reducing ‘piles’ and vibro stone columns, are available for improving strength of weak soils. These techniques are mainly used to reduce the applied pressure on soft soils without altering the soil structure significantly. Several piled-embankment design procedures (i.e. Hewlett and Randolph, 1988 and the German method (EBGEO), 2004) currently used by industry appear to yield significant difference in predicting the load transfer mechanism within the embankment material due to lack of modelling various aspects of the embankment geometry, soil properties, and load transfer mechanism with the embankment material.